Modernising educational programmes in ICT based on the Tuning methodology - Alexander Bedny; Liliya Erushkina; Oleg Kuzenkov (Universidad de Deusto, 2014)
An analysis is presented of the experience of modernising undergraduate educational programs using the TUNING methodology, based on the example of the area of studies "Fundamental computer science and information technology" (FCSIT) implemented at Lobachevsky State University of Nizhni Novgorod (Russia). The algorithm for reforming curricula for the subject area of information technology in accordance with the TUNING methodology is explained. A comparison is drawn between the existing Russian and European standards in the area of ICT education, including the European e-Competence Framework, with the focus on relevant competences. Some guidelines for the preparation of educational programmes are also provided.